Analyses of a Ceftazidime-Avibactam-Resistant Citrobacter freundii Isolate Carrying blaKPC-2 Reveals a Heterogenous Population and Reversible Genotype - Mariana Castanheira (American Society for Microbiology, 2018)
ABSTRACT A blaKPC-2-carrying Citrobacter freundii isolate developed ceftazidime-avibactam resistance during treatment with this agent. The initial and follow-up isolates exhibited ceftazidime-avibactam MICs of 4 and 64 µg/ml, respectively. Overexpression of AcrAB-TolC and porin alterations were detected in both isolates, but no other resistance mechanism was observed. After passaging the initial clinical isolate in ceftazidime-avibactam at a fixed concentration of 4 µg/ml and a 4:1 ratio, resistance to all β-lactams was noted, and a percentage of the blaKPC-2 sequencing reads had mutations leading to the alterations D176Y (blaKPC-2-D176Y [78%]) or R164S plus P147L (blaKPC-2-R164S + P147L [82%]). Further investigation of the follow-up isolate showed that 11% of the blaKPC-2 reads had mutations leading to D179Y substitution (blaKPC-2-D179Y). In the absence of selective pressure, ceftazidime-avibactam MICs of the passaged and follow-up isolates revealed that 7 or 8 out of 20 screened colonies reverted to susceptible and possessed blaKPC-2 wild-type sequences. Recombinant plasmids carrying the blaKPC-2 alterations observed were transformed in Escherichia coli, and MIC values for ceftazidime ± avibactam were elevated. Lower MICs for ceftriaxone, cefepime, aztreonam, meropenem, and imipenem for the mutated KPC-2-producing isolates were observed compared to those of the isolates producing a wild-type KPC-2. Avibactam at a fixed concentration of 4 µg/ml restored the activity of all β-lactams tested for the recombinant strains. The heterogenous population of wild-type and mutated blaKPC-2 and the reversibility of the genotypes observed suggest a significant challenge for managing KPC-producing isolates that develop ceftazidime-avibactam resistance during therapy. IMPORTANCE The development of ceftazidime-avibactam resistance among KPC-producing isolates during treatment with this agent has been reported. Usually isolates that become resistant have a mutated blaKPC gene that confers resistance to ceftazidime-avibactam and susceptibility to meropenem. We report a Citrobacter freundii isolate that developed ceftazidime-avibactam resistance due to mutations within the coding region of the blaKPC-2 Ω-loop previously reported; however, in this case, only 11% of the whole-genome sequencing reads had mutations, making this alteration difficult to detect and the treatment of these isolates more challenging. In addition to blaKPC, the initial and the follow-up patient isolates displayed hyperexpression of the AcrAB-TolC efflux system and disruption of the outer membrane protein (OMP) OmpF, which contribute to carbapenem resistance. Experiments performed to confirm our findings included generating mutant isolates from the initial patient isolate, passaging the isolates for purity in drug-free medium, resulting in a reversible phenotype, and cloning the mutations to demonstrate the resistance conferred.